Ultra-high pressure direct syntheses of bis(imidazolium-3-yl)alkane dichlorides. Issue 44 (1st November 2019) - Harwood, Laurence M.; Pitt, Phillip; Scott, Janet L.; Sousa, Dora
Abstract: The ultra-high pressure Menshutkin reaction of N-substituted imidazoles and α, ω-dichloroalkanes provides access to a wide variety of bis(imidazoliumyl)alkane dichlorides in an efficient, one-pot process. Although the substitution reactions of dichloromethane at ambient pressure can be exceedingly slow, at 1.9 GPa, syntheses are usually quantitative in under 24 h. Reactions involving congested imidazole starting materials, that otherwise terminate after formation of the mono-imidazolium salt, are driven to the bis-imidazolium salt at 1.9 GPa. The rates of reaction increase with α, ω-dichloroalkane chain length, decrease with increasing bulk and imidazole N-substituent length, and the reactions of the more hindered imidazoles are more sensitive to the pressure-rate enhancement. Graphical abstract: Image 1 Highlights: The Menshutkin reaction is strongly accelerated by ultra high pressures. Reactions of dichloromethane were generally rapid and high yielding. Product distribution is shifted towards the bis(imidazolium) salt. Steric effects on the rate of reaction clearly demonstrated.